Intercambio epistolar entre Hugo Blanco y José María Arguedas (noviembre 1969) - Hugo Blanco; José María Arguedas (Les Cahiers ALHIM)
Two prominent Quechua speakers had an epistolary exchange in 1969. At this moment, Hugo Blanco was in jail and José Maria Arguedas was in a depressive state. Their letters convey tenderness, personal adventures, and involvement in the Quechua culture and defiance.